KONFLIK PERAN GANDA, LOCUS OF CONTROL INTERNAL, DAN KEPUASAN KERJA PADA KARYAWAN WANITA - Prestiana, Novita Dian Iva; Marzuki, Abid (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2015)
Nowadays wives do not just act as a full housewife, but also helps her husband to make a living. Such conditions often affect the conflicts experienced by working mothers. Perceived conflicts working mothers usually can affect relationships with family and relationship with the company. The purpose of this study is to conduct further study on the relationship between dual role conflict and internal locus of control and job satisfaction of the employee. The population used in this study were all employee. Sampling was done by purposive random sampling. Regression analysis through ANOVA test showed no relationship between internal locus of control, dual role conflict, job satisfaction